Dyspepsia: An Integrated Review of Diagnosis, Classification, and Mechanisms of Modern and Herbal Medications - Citra Kurnia Solihat; Citra Kurnia Solihat; Fita Rahmawati; Soni Siswanto (Majalah Farmaseutik, 2026)
Dyspepsia is a common and complex disorder characterized by symptoms such as epigastric pain, bloating, and early satiety, which significantly impact patients' quality of life. The pathophysiology of dyspepsia remains poorly understood, with multiple underlying factors including Helicobacter pylori infection, gastric motility disturbances, and visceral hypersensitivity. Modern therapeutic strategies primarily focus on acid suppression and motility enhancement, with Proton Pump Inhibitors (PPIs), H2 blockers, and prokinetic agents as standard treatments. The advent of novel therapies, such as potassium-competitive acid blockers (P-CABs) like Tegoprazan, offers promising alternatives with faster onset and longer-lasting effects. Herbal therapies, including turmeric, ginger, and licorice, have also been explored, showing potential benefits in symptom relief and gastric protection. Despite these advances, the effectiveness of treatment remains variable, and a tailored approach based on patient-specific factors is recommended. This review highlights the current treatment modalities, including both modern and traditional approaches, with a focus on pharmacological and non-pharmacological therapies for dyspepsia.